The Relationship Between White Matter Microstructure and General Cognitive Ability in Patients With Schizophrenia and Healthy Participants in the ENIGMA Consortium - Holleran, Laurena; Kelly, Sinead; Alloza, Clara; Agartz, Ingrid; Andreassen, Ole A; Arango, Celso; Banaj, Nerisa; Calhoun, Vince; Cannon, Dara; Carr, Vaughan; Corvin, Aiden; Glahn, David C; et al. (The American journal of psychiatry, 2020)
OBJECTIVE: Schizophrenia has recently been associated with widespread white matter microstructural abnormalities, but the functional effects of these abnormalities remain unclear. Widespread heterogeneity of results from studies published to date preclude any definitive characterization of the relationship between white matter and cognitive performance in schizophrenia. Given the relevance of deficits in cognitive function to predicting social and functional outcomes in schizophrenia, the authors carried out a meta-analysis of available data through the ENIGMA Consortium, using a common analysis pipeline, to elucidate the relationship between white matter microstructure and a measure of general cognitive performance, IQ, in patients with schizophrenia and healthy participants. METHODS: The meta-analysis included 760 patients with schizophrenia and 957 healthy participants from 11 participating ENIGMA Consortium sites. For each site, principal component analysis was used to calculate both a global fractional anisotropy component (gFA) and a fractional anisotropy component for six long association tracts (LA-gFA) previously associated with cognition. RESULTS: Meta-analyses of regression results indicated that gFA accounted for a significant amount of variation in cognition in the full sample (effect size [Hedges' g]=0.27, CI=0.17-0.36), with similar effects sizes observed for both the patient (effect size=0.20, CI=0.05-0.35) and healthy participant groups (effect size=0.32, CI=0.18-0.45). Comparable patterns of association were also observed between LA-gFA and cognition for the full sample (effect size=0.28, CI=0.18-0.37), the patient group (effect size=0.23, CI=0.09-0.38), and the healthy participant group (effect size=0.31, CI=0.18-0.44). CONCLUSIONS: This study provides robust evidence that cognitive ability is associated with global structural connectivity, with higher fractional anisotropy associated with higher IQ. This association was independent of diagnosis; while schizophrenia patients tended to have lower fractional anisotropy and lower IQ than healthy participants, the comparable size of effect in each group suggested a more general, rather than disease-specific, pattern of association.
Keywords: bílá hmota; Wechsler Scales; Anisotropy; Male; Middle Aged; Brain; Schizophrenia; ENIGMA; Adult; Case-Control Studies; dospělí; zobrazování difuzních tenzorů; mužské pohlaví; Neural Pathways; Healthy Volunteers; analýza hlavních komponent; faktorová analýza statistická; Schizophrenic Psychology; Principal Component Analysis; Meta-Analysis; Factor Analysis, Statistical; kognice; schizofrenie (psychologie); lidé; Intelligence; Diffusion Tensor Imaging; ženské pohlaví; studie případů a kontrol; Humans; anizotropie; inteligence; White Matter; schizofrenie; nervové dráhy; mozek; zdraví dobrovolníci pro lékařské studie; Wechslerovy škály; Female; lidé středního věku; Cognition